Enhanced Biodegradation of DDT by White-Rot Fungus Phlebia brevispora TMIC34596 in a Nutrient-Rich Medium at Short Incubation Time - Boelan, Erly Grizca; Purnomo, Adi Setyo; Fajriah; Kamei, Ichiro; Leba, Maria Aloisia Uron; Missa, Hildegardis; Baunsele, Anselmus Boy; Kopon, Aloysius Masan (HAYATI Journal of Biosciences, 2026)
1,1,1-Trichloro-2,2-bis(4-chlorophenyl) ethane (DDT) is a persistent organic pollutant that remains a global environmental concern due to its high toxicity and recalcitrance. This study investigated the ability of the white-rot fungus Phlebia brevispora to degrade DDT in a nutrient-rich Potato Dextrose Broth (PDB) medium under a short incubation time. The fungus degraded 64.25% of DDT within 7 days. Metabolites identified by GC/MS were DDE (1,1-dichloro-2,2-bis(4-chlorophenyl) ethylene), DDD (1,1-dichloro-2,2-bis(4-chlorophenyl) ethane), and DDMU (1-chloro-2,2-bis(4-chlorophenyl) ethylene), indicating both reductive dechlorination and dehydrogenation pathways. The results demonstrate that P. brevispora has strong potential for rapid biotransformation of DDT in nutrient-rich environments.